Computational investigations on efficient metal-free organic D-π-A dyes with different spacers for powerful DSSCs applications. Issue 2 (22nd January 2022) - Anbarasan, P.M.; Arunkumar, A.; Shkir, Mohd
ABSTRACT: Based on 3-(4-((4-carbazol-9-yl-phenyl)ethynyl)phenyl)-2-cyanoacrylic acid (CB1) dye, the six newly planned organic spacer (CBS1-CBS6) dyes were investigated for dye-sensitised solar cell (DSSC) application. The designed dyes have an electron-donor (D) in carbazole through a different π-spacer and an electron-acceptor (A) in 2-cyanoacrylic acid. The density functional theory (DFT) and the time-dependent DFT (TD-DFT) evaluated the DSSCs of the molecules in the strategic platform. The results display that the TD-DFT method, using different functionals with exchange (XC) and long-range correlated (LC), was discussed. The electronic and optical properties of the CBS1-CBS6 dyes were discussed. The highest occupied molecular orbitals (HOMOs) and lowest unoccupied MOs (LUMOs) of the CBS1-CBS6 molecules can confirm the probable response to the regeneration and electron injection process. Also, the calculated results, such as injection driving force ( Δ G inject ), light-harvesting efficiencies ( LHE ), regeneration ( Δ G reg ) and open-circuit photovoltage ( V O C ) of the CBS1-CBS6 sensitisers, were presented. A good contract of theoretical calculations with the literature data reveals a better understanding of the spacer's PV performance. To conclude, benzo[c][1, 2, 5]oxadiazole (CBS2) and [1, 2, 5]oxadiazolo[3, 4-c]pyridine (CBS5) spacers were the best candidates for DSSCs, because of their smaller energy gap ( E g ) and red-shifted absorption wavelengths.